2013
DOI: 10.5812/asjsm.34283
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Serum Retinol Binding Protein 4 Levels Following 8 Weeks Moderate Aerobic Exercise

Abstract: Purpose: The purpose of this study was to examine the effects of 8 weeks moderate intensity aerobic exercise on serum retinol binding protein 4 (RBP4) levels in female athletes.Methods: Twenty female karate athletics were randomly assigned to one of the exercise group (n=10) or control group (n=10). The training group performed endurance training 3 days a week for 8 weeks at an intensity corresponding to 50-60% individual maximum oxygen consumption for 45 min.Results: Body mass and body mass index increased (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
4
2
Order By: Relevance
“…Some studies have proposed FABP changes after exercise stemmed from changes in fat mass and body fat percent-age following exercise (29). Contrary to the findings of this study, there was no significant effect on the serum level of RBP-4 in athletes after eight weeks of training in a previous study (30). It seems that lower RBP-4 concentrations in athletes compared to diabetics patients and those with impaired glucose tolerance can be a reason for insignificant effect of training (30).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some studies have proposed FABP changes after exercise stemmed from changes in fat mass and body fat percent-age following exercise (29). Contrary to the findings of this study, there was no significant effect on the serum level of RBP-4 in athletes after eight weeks of training in a previous study (30). It seems that lower RBP-4 concentrations in athletes compared to diabetics patients and those with impaired glucose tolerance can be a reason for insignificant effect of training (30).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the findings of this study, there was no significant effect on the serum level of RBP-4 in athletes after eight weeks of training in a previous study (30). It seems that lower RBP-4 concentrations in athletes compared to diabetics patients and those with impaired glucose tolerance can be a reason for insignificant effect of training (30). This discrepancy in results could be attributed to the type and intensity of the training, sampling time after the last training session and the physical condition of the subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, running on treadmill resulted in a reduction in protein and gene expression of RBP4 in serum [ 18, 19 ] and visceral and subcutaneous fat tissue in diabetic [ 2 ] and spontaneously hypertensive [ 18, 19 ] rats. In contrast, in other studies, it has been reported that neither moderate to intensive aerobic exercise [ 4 , 6 , 17 ] nor walking exercise [ 16 ] had any significant effect on fasting glucose, insulin, resistance insulin, and circulating levels of RBP4 in females with type 2 diabetes [ 16, 17 ] and healthy athletes [ 4, 6 ].…”
Section: Introductionmentioning
confidence: 95%
“…There is now a substantial body of evidence to suggest that destruction of beta cell, decreased levels of insulin and its receptors, and decreased content of glucose transporters (GLUTs) resulted in insulin resistance [ 1–3 ]. Current evidence has reported that retinol-binding protein 4 (RBP4) is also one of the mechanisms involved in the incidents of diabetes [ 2 , 4–6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation